Studies on the landscape history of the Tölgy-erdő in Lébény - Selmeci, Marianna; Höhn, Mária; Saláta, Dénes (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
The Tölgy-erdő near Lébény village (W-Hungary) is an area rich in nature and culture, located on the eastern periphery of the Hanság territory, being under nature conservation. Two types of threatened habitats exist on the research area: Circaeo-Carpinetum and Pimpinello majoris-Ulmetum woodlands. Our aim was to study the landscape history and reconstruct the forest use history of the forest. The changing in time and the history of forest use were chronologically ordered by the use of literature sources, archive documents and reports of local inhabitants. Results of historical research were supported with historical maps and archive aerial photos with the highlighting of matching forest management plans with archive aerial photos. Significant changes in the state of the forest were started after 1952 and escalated in the 70’s. 108 vascular plant species have been listed based on literature and own field research. 6 habitat types were identified they are presented on a habitat map in parallel with the present state of the vegetation. We have realized that the habitats in the best naturalness state are situated in the eastern and north-eastern part of the forest.
Keywords: landscape history; forest-use history; Lébény; Győr basin; remnant woodland